Pengaruh Curah Hujan terhadap Tinggi Muka Air Tanah Gambut Saat Fenomena El Nino di Sub Kesatuan Hidrologis Gambut Sungai Mendahara-Sungai Lagan - Suwananda, Erik; Saad, Asmadi; Aswandi, Aswandi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze the effect of rainfall on the peat groundwater level (GWL) in the Mendahara River-Lagan River Peat Hydrological Sub Unit (sub KHG) during the El Nino phenomenon. The analysis was carried out using a simple linear regression method on 3 dominant land covers, namely private oil palm plantations, community oil palm plantations and secondary swamp forests, where 2023 is an El Nino year. The results of the research show that in the year private oil palm plantation land cover had the strongest influence on the amount of rainfall distribution compared to community oil palm plantation land cover and secondary swamp forest with R2 values of 76.14%, 58.03% and 51,42%. The value of the coefficient of determination (R2) means that the dynamics of TMAT fluctuations can be explained by the amount of rainfall distribution, while the rest is influenced by other variables not studied.